Hold-up Problems with Respect to R&D Investment and Licensing in Environmental Regulation - Jörg Breitscheidel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
We explore the design of self-financing tax-subsidy schemes to solve hold-up problems in environmental regulation. The announcement of the tax rate seems to be preferable to solve hold-up problems with respect to the investment in environmental R&D. In contrast, only the announcement of the subsidy rate is adequate to solve hold-up problems with respect to the licensing of environmentally friendly technologies. Altogether, the announcement of the subsidy rate yields higher expected social welfare than the announcement of the tax rate or the standard emission taxation if the marginal damage of emissions exceeds a certain level.
Keywords: D43; Q28; L50; D62; 330; Hold-up problems; Environmental regulation; Taxes and subsidies; Selffinancing mechanisms; Emission control; Umweltpolitik; Umweltschutzinvestition; Sunk Costs; Investition; Umweltökonomik; Ökonomischer Anreiz; Duopol; Oligopol; Wohlfahrtseffekt; Theorie; Industrielle Forschung; hold-up